IMPLEMENTASI TA’ZIR DALAM UPAYA MENINGKATKAN KEDISIPLINAN SANTRI DI PONDOK ROUDLATUL ROHMANIYAH SUKOLUMAJANG - Al Musdhaqiron, Muhammad (Dakwah, 2017)
This study is conducted to find out the implementation of Ta'zir in improving the discipline of santri(student) in Raudlatur Rohmaniah Islamic boarding school in Suko Lumajang. The type of research used in this study is descriptive research, namely an approach to behavior, phenomena, events, problems or certain circumstances that became objects investigation; which the results are all descriptions of sentence that explain certain understandings. The results of the study shows that the implementation of Ta'zir in Raudlatul Rohmaniyah Islamic boarding school in Suko Lumajang has been quite effective in developing the discipline of santri in learning as well as in preparingthem to associate within thesociety.